A broadband circularly polarized stacked microstrip patch antenna with parasitic elements. Issue 11 (10th August 2021) - Dai, Wen‐Juan; Huang, Zhi‐Fang
Abstract: In this article, a wideband circularly polarized stacked microstrip patch antenna (CP SMPA) with continuous phase feed characteristics is presented. The designed antenna consists of a square‐loop feeding structure as driven element, four rectangular‐patches and four rotated square‐patches as parasitic elements. First, a square‐loop with arc‐shaped strip is designed to obtain 90° phase difference. Second, four rectangular‐patches are placed next to the square‐loop for generating a CP resonant mode through a capacitive coupling method. Third, four rotated square‐patches are arranged at the top of the rectangular‐patches to excite an additional CP resonant mode. Eventually, the designed CP SMPA features a wide −10‐dB impedance bandwidth (IBW) of 32% (5.93 GHz, 4.98–6.88 GHz), and a broad 3‐dB axial ratio bandwidth of 22.8% (6.15 GHz, 5.45–6.85 GHz).